Quantification of the adhesion strength of fibroblast cells on ethylene glycol terminated self-assembled monolayers by a microfluidic shear force assay - Christophis, Christof; Grunze, Michael; Rosenhahn, Axel (Physical chemistry, chemical physics, 2010)
The adhesion strength of cells depends on the properties of the surface they attach to. Varying the surface properties can trigger different cellular responses such as differentiation. In order to study cell adhesion quantitatively, we developed a microfluidic shear force assay which allows the variation of applied shear stress by five orders of magnitude. With this device we can determine the critical shear stress which is necessary to remove 50% of the adherent cells. As an application we investigated the adhesion strength of cells on a series of oligo(ethylene glycol) (OEG) containing self-assembled monolayers (SAMs). By varying the number of ethylene oxide units, the hydration properties of the monolayers are changed. We found that cell adhesion strength for mammalian fibroblasts decreases if the hydration of the surface is increased. As the cell spreading area changes with the substrate properties, the adhesion strength per unit area was additionally determined.
Gesehen am 21.03.2023